2014
DOI: 10.1186/1749-8104-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression profile of the response to spinal cord injury in Xenopus laevis reveals extensive differences between regenerative and non-regenerative stages

Abstract: BackgroundXenopus laevis has regenerative and non-regenerative stages. As a tadpole, it is fully capable of functional recovery after a spinal cord injury, while its juvenile form (froglet) loses this capability during metamorphosis. We envision that comparative studies between regenerative and non-regenerative stages in Xenopus could aid in understanding why spinal cord regeneration fails in human beings.ResultsTo identify the mechanisms that allow the tadpole to regenerate and inhibit regeneration in the fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 70 publications
(74 reference statements)
5
76
0
Order By: Relevance
“…All animal procedures were approved by the Committee on Bioethics and Biosafety from the Faculty of Biological Sciences, Pontificia Universidad Católica de Chile. For spinal cord transection, tadpoles and froglets were operated as described (Gaete et al, 2012; Lee-Liu et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All animal procedures were approved by the Committee on Bioethics and Biosafety from the Faculty of Biological Sciences, Pontificia Universidad Católica de Chile. For spinal cord transection, tadpoles and froglets were operated as described (Gaete et al, 2012; Lee-Liu et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…In froglets we isolated the segment from the hindbrain, including the gap area, to the end of the spinal cord (approximate of 3 mm long). For RT-qPCR we isolated a fragment from the midpoint of the transection site (Lee-Liu et al., 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual cessation of regenerative capacity at the onset of metamorphosis is studied mostly in the African clawed toad (Xenopus laevis) (Bernardini et al, 2010;Lee-Liu et al, 2014;Yoshino and Tochinai, 2004). Interestingly, there is also a non-regenerative period during larval development of the Xenopus tadpole, before and after which tail regeneration, including spinal cord, occurs (Beck et al, 2003).…”
Section: Types and Extent Of Neuronal Regeneration In The Cns Of Anammentioning
confidence: 98%
“…Various publications suggest that blastema contains dedifferentiated (Bellairs and Bryant, 1985;Carlson, 2011) or likely undifferentiated cells (Butler, 1935;Gurley and Alvarado, 2008;Tweedell, 2010), whereas different appendage regeneration studies showed that blastema tissues consisted of a heterogeneous population of different lineage restricted stem/progenitor cells (Kragl et al, 2009;Rinkevich et al, 2011;Lee-Liu et al, 2014). The later cell types have various origins and are not capable of differentiating into cells originated from other germ layers (Kragl et al, 2009;Rinkevich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%